2003
DOI: 10.1084/jem.20020906
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Interleukin (IL)-13 Responses in Mice Lacking IL-13 Receptor α 2

Abstract: Interleukin (IL)-13 has recently been shown to play important and unique roles in asthma, parasite immunity, and tumor recurrence. At least two distinct receptor components, IL-4 receptor (R)α and IL-13Rα1, mediate the diverse actions of IL-13. We have recently described an additional high affinity receptor for IL-13, IL-13Rα2, whose function in IL-13 signaling is unknown. To better appreciate the functional importance of IL-13Rα2, mice deficient in IL-13Rα2 were generated by gene targeting. Serum immunoglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
132
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(145 citation statements)
references
References 39 publications
10
132
1
2
Order By: Relevance
“…Recent data have clearly shown that a second IL-13R acts as a regulator of IL-13-induced inflammation (49,50). Soluble IL-13R␣2 binds IL-13 with high affinity, but does not provide a signal (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have clearly shown that a second IL-13R acts as a regulator of IL-13-induced inflammation (49,50). Soluble IL-13R␣2 binds IL-13 with high affinity, but does not provide a signal (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…IL-13-deficient mice and IL-4/IL-13-double deficient mice (48) were a gift from Dr. A. McKenzie (Medical Research Council Laboratory of Molecular Biology, Cambridge, U.K.). IL-13R␣2-deficient mice (49) and Stat6-deficient mice (C.129S2-Stat6 tm1Gru/J ) (18) were a gift from M. Grusby (Harvard University, Boston, MA). IL-13/IL-13R␣2-double deficient mice were generated by breeding IL-13-and IL-13R␣2-deficient mice.…”
Section: Micementioning
confidence: 99%
“…In particular, IL-13R 2 chain has a unique property of ligand internalization after binding, 36,37 which has also been identified as a soluble protein in mouse serum and urine; 38 thus, it can be a specific inhibitor of IL-13 signaling or a decoy receptor for IL-13. [39][40][41] Moreover, IL-13R 2 chain may inhibit IL-13-mediated biologic functions in tumor growth and recurrence. 26,27,42,43 To utilize the attractive properties of IL-13R 2 chain in IL-13 cytotoxin-mediated cancer therapy, we previously tried to combine the cytotoxin treatment with gene transfer of IL-13R 2 chain.…”
mentioning
confidence: 99%